The use of ATC/DDD WHO 2016 and Prescription audit study in the Dermatology OPD of a tertiary care hospital in Jharkhand - Mishra, Priyanki; Suman, Shruti; Kesri, Umashanker; Mishra, Pranay Kumar; Kumari, Kusum (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To study the prescribing patterns, rationale of drug usage and use of anatomical, therapeutic, chemical (ATC) and defined daily dosage (DDD) classification for the monitoring of drug utilization in the dermatology department of a tertiary care hospital. Methods: A retrospective, observational study was conducted in out-patients department of dermatology at RIMS, Ranchi over a period of two months. Rationale of drug usage was assessed by analysing the prescriptions. Defined daily dosage/1000 patients/day of the commonly used medications was compared to the defined daily dosage by World Health Organization in 2016. Data was analysed by statistical tools. Most of the results were expressed in percentages. Results: The prescriptions were rational in most of the cases. Emphasis was more towards the branded drugs. Polypharmacy was evident in many of the prescriptions. The number of DDD/1000 patients/day in cases of antifungals was more than the WHO DDD and less than the WHO DDD in case of antihistaminics. Conclusions: The number of drugs per prescription must be rationalized so as to avoid polypharmacy. The drugs should be prescribed by their generic names also along with the brand names. Generic medicines should be available in the hospital pharmacy so that a more cost-effective treatment can be assured. CMEs and stewardship programs for health care professionals regarding rational drug usage should be organized.